Pengaruh Motivas Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Generasi Milenial Pada Kabupaten Dompu: The Influence of Work Motivation and Work Environment on The Performance Of Millennial Generation Employees in Dompu Regency - Sari, Indah; Aprianti, Kartin; Mulyadin, Mulyadin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to determine the effect of work motivation and work environment on the performance of millennial generation employees in Dompu Regency. The research instrument used a Likert scale questionnaire. Sampling was carried out using purposive sampling to obtain a sample of 96 respondents using the Lemeshow formula. Data collection techniques used observation, questionnaires, and literature studies. Analysis used multiple linear regression. The results of the study indicate that both partially and simultaneously, work motivation and work environment have a significant effect on the performance of millennial generation employees in Dompu Regency.